Effectiveness of Digital Management System In Improving Employee Performance at The Mayor's Office of Parepare - Mulono Apriyanto; Aep Saefullah; Wildan F Mubarock; Khairul Anwar; Albi Ternando; Jornie Lumintao; Nada Ratković (Marsiurupan: Journal of Community Development and Empowerment, 2026)
The development of digital technology has changed the way government operates, including the Parepare Mayor's Office, which faces challenges in increasing the efficiency and effectiveness of employee performance. This research aims to assess the implementation of a digital management system as a solution to overcome the problems of manual bureaucracy, miscommunication, and lack of data integration. The methods used in this research include observation and interviews with employees from various divisions, as well as quantitative and qualitative analysis to measure system effectiveness through key performance indicators (KPI). The research results show that the implementation of a digital management system has succeeded in increasing work efficiency, transparency and accuracy, with an increase in employee productivity reaching 60% and job satisfaction levels of 85%. Despite challenges such as inadequate infrastructure and resistance to new technology, this program has succeeded in creating a digital-based work culture